An Analytical Study of the Accounting Practices for Income Tax in the Light of the Algerian Accounting System Based on IAS/IFRS: The Case of Algerian Companies - Mameche, Youcef (Jordan Journal of Business Administration, 2018)
This paper comes to analyze and translate, in the business environment of Algeria, findings relating to the reality of the accounting practices regarding the deferred tax approach, as stipulated by the new Algerian financial accounting system and IAS 12 "income tax", on the basis of data obtained from the Algerian economic environment. On other hand, the study aims to investigate the relationship between firm characteristics and the level of its compliance with the deferred tax method. To achieve these objectives, the researcher conducted an empirical study on a sample of professional accountants working at a number of private, public and mixed Algerian companies operating in different economic sectors. So, this study goes together with a specifically designed questionnaire as a research instrument to answer the study questions. 170 questionnaires were distributed randomly to the respondents. 12 questionnaires were excluded because they were not valid for statistical analysis and 158 questionnaires were selected for statistical analysis, representing (92%) of the study sample. For the purpose of data analysis, a number of statistical methods have been used (descriptive statistics, one-sample t-test and Pearson correlation coefficient). The findings showed that the large majority of Algerian companies do not comply with the deferred tax method stipulated by the new Algerian financial accounting system and IAS 12. The reason is that tax legislations do not require to apply deferred tax method, in addition to lack or weakness of academic education and professional training by Algerian accountants. Moreover, this non-compliance could be explained by the fact that benefits arising from the application of the deferred tax method are less than costs incurred by Algerian firms for the application of this method. The findings also revealed non-compliance of the Algerian accounting practices regarding the deferred tax approach with international accounting standard requirements in terms of: the approach adopted for the application of the deferred tax method, accounting recognition of deferred tax and valuation of deferred tax. Another finding of this study states that the relationship between firm characteristics and the level of its compliance with the deferred tax method is not statistically significant. The study therefore recommended that education and training of Algerian professional accountants should be strengthened. It also pointed out the role of legal auditors and the importance of the legislative tax framework as well as the weight of tax incentive factor to support Algerian companies to comply with the deferred tax method, especially since Algeria is considered to have a tax -oriented accounting system culture in the absence of an effective Algerian market.